PERSEPSI MASYARAKAT DAN PERUSAHAAN TERHADAP PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PT BUKIT ASAM UNIT PELABUHAN TARAHAN, KOTA BANDAR LAMPUNG - Fadlan Satria; Dewangga Nikmatullah; Indah Nurmayasari (Lampung University, 2018)
CSR (Corporate Social Responsibility) is a vital element for company in order to manage good relationship with local people and surroundings. CSR were made to maintain the balance between corporate interests and the welfare of surrounding community. Hence, this study aims to find out the level of CSR Program implementation at PT Bukit Asam Unit Pelabuhan Tarahan, the perception of society and company, and the relationship between the perception and the level of the CSR Program implementation. The location of this study has been chosen puposively in Tarahan Village, Panjang Subdistrict, Bandar Lampung. Respondents of this research were 61 of local people and 6 of company staffs. Data were collected in April - May 2017. This research used a survey method with descriptive analysis and used nonparametric statistics test correlation Rank Spearman to test the hypothesis. The results showed that the level of program implementation is in a high classification, the perception of society on CSR Program is in good classification, the perception of company to CSR Program is also in good classification. There is no significant correlation between the perception of society and program implementation, in other hand there is significant correlation between the perception of company and program implementation of PT Bukit Asam Unit Pelabuhan Tarahan. Key words: CSR Program, the perception of society, the perception of company